1993
DOI: 10.1111/j.1540-6261.1993.tb04703.x
|View full text |Cite
|
Sign up to set email alerts
|

Hot Hands in Mutual Funds: Short‐Run Persistence of Relative Performance, 1974–1988

Abstract: The relative performance of no-load, growth-oriented mutual funds persists in the near term, with the strongest evidence for a one-year evaluation horizon. Portfolios of recent poor performers do significantly worse than standard benchmarks; those of recent top performers do better, though not significantly so. The difference in risk-adjusted performance between the top and bottom octile portfolios is six to eight percent per year. These results are not attributable to known anomalies or survivorship bias. Inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
136
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 829 publications
(146 citation statements)
references
References 31 publications
9
136
0
1
Order By: Relevance
“…Thus, we repeat our persistence tests for 1-year periods and class-A shares exclusively and find that a winner-picking strategy yields an abnormal return of about 1.7% annually. This is in agreement with the results in Hendricks et al (1993). Overall, we think that these results lend support to Gruber's clientele hypothesis presented in Gruber (1996).…”
supporting
confidence: 94%
“…Thus, we repeat our persistence tests for 1-year periods and class-A shares exclusively and find that a winner-picking strategy yields an abnormal return of about 1.7% annually. This is in agreement with the results in Hendricks et al (1993). Overall, we think that these results lend support to Gruber's clientele hypothesis presented in Gruber (1996).…”
supporting
confidence: 94%
“…Thus, funds that record positive persistence in the past will have a higher chance of attracting huge net inflows, which, in turn, lead to increase the fund unit price. This finding is in line with the results of the study by Hendricks et al (1993) who found stronger evidence that funds that do well in the past do well in the short-term future. Further, this is supported by Goetzmann and Ibbotson (1994), who suggested that past mutual fund returns could predict future returns.…”
Section: Journal Of Management Researchsupporting
confidence: 83%
“…Hendricks et al (1993) and Goetzmann and Ibbotson (1994), among others, document persistent performance in mutual funds from one period to another. Although Carhart (1997) shows that a strategy that buys the top decile of mutual funds based on their last year's performance and shorts the bottom decile of mutual funds yields an 8% return, momentum in stocks as documented by Titman (1993, 2001) help explain part of this abnormal return along with other common risk factors in stock returns.…”
Section: Momentum In Stock Pricesmentioning
confidence: 94%